Agama dan Pembangunan Ekonomi Modern: Integrasi Nilai Islam dengan SDGs dan Inclusive Growth - Katamso, Rudi; Zainal Abidin, Yusuf; Kusnawan, Aep; Zuldin, Muhamad (Jurnal Ilmu Sosial dan Humaniora, 2025)
Modern economic development is no longer understood solely as economic growth but as a multidimensional process encompassing improvements in welfare, distributive justice, human development, and sustainability. Islam, as a value-based system, offers a strong normative framework for development, particularly through the principles of maqasid al-shari‘ah, distributive justice, the prohibition of usury (riba), the obligation of zakat, and the reinforcement of ethical economic conduct. This study examines the relationship between religion and modern economic development using a qualitative-comparative approach between Islamic teachings and contemporary development concepts such as the Sustainable Development Goals (SDGs), the Human Development Index (HDI), Good Governance, and Inclusive Growth. The findings indicate that Islam demonstrates structural compatibility with modern development paradigms, especially in poverty alleviation, social justice, economic governance, and social capital enhancement. Islam functions not only as a moral guide but also provides concrete economic instruments such as zakat, productive waqf, Islamic finance, Islamic social finance, and halal digital economic models. Thus, religion plays a strategic role in building a more inclusive, ethical, and sustainable economic order.